The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14112724
|View full text |Cite
|
Sign up to set email alerts
|

Promising Green Technology in Obtaining Functional Plant Preparations: Combined Enzyme-Assisted Supercritical Fluid Extraction of Flavonoids Isolation from Medicago Sativa Leaves

Abstract: To elaborate a complete extraction protocol for the enhanced release of biologically active compounds from plant cells, this study aimed to optimize together the parameters of the supercritical fluid extraction (SFE) process (temperature, pressure, and percentage of cosolvent) and enzymatic treatment of plant material (pH, enzyme concentration, time, and temperature) by response surface methodology (RSM). Medicago sativa L. was selected as a plant material due to its richness in phenolics and flavonoids. HPLC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…The PCA analysis illustrated that the AOA of the bound extracts was mainly attributed to the phenolics, which is confirmed by their strong correlation (r = 0.822, Table S5 ). This observation is in agreement with others [ 31 , 35 ]. The distance between TPC and their AOA in soluble extract indicates those other compounds acting as antioxidants, rather than the identified phenolics [ 29 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The PCA analysis illustrated that the AOA of the bound extracts was mainly attributed to the phenolics, which is confirmed by their strong correlation (r = 0.822, Table S5 ). This observation is in agreement with others [ 31 , 35 ]. The distance between TPC and their AOA in soluble extract indicates those other compounds acting as antioxidants, rather than the identified phenolics [ 29 ].…”
Section: Resultssupporting
confidence: 94%
“…), used analytical technique (HPLC, HPLC-MS, HPLC-MS/MS, etc. ), and alfalfa part (aerial or roots) [ 16 , 35 , 36 ]. Newby et al [ 37 ] determined the dominance of alkali-labile bound phenolic acids in relation to soluble ones (less than 2%).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its high extraction efficiency and high purity of extracts, SFE is widely used to extract bioactive compounds from various substances. SFE has been used to extract and analyze natural products, allowing the extraction of aroma compounds with high purity and freshness to determine the compounds conferring the flavor characteristics of plants 81,82 . In addition, SFE is referred to as a ‘green technology’ owing to its benefits in terms of environmental protection and recycling.…”
Section: Methods For Detecting Fruit Aroma Compoundsmentioning
confidence: 99%
“…It has also been shown that the initial treatment of plant material with an enzyme preparation commonly used in the agricultural industry significantly increased the efficiency of the extraction of bioactive substances. The use of enzyme-assisted supercritical fluid extraction in various industries to isolate bioactive compounds from plant material is economically effective and represents an advance in modern technological processes [ 12 , 114 ].…”
Section: The Concept Of Enzymes and Enzymatic Extractionmentioning
confidence: 99%